PENGARUH PENGUNGKAPAN MODAL INTELEKTUAL TERHADAP COST OF EQUITY PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Putri Larasati; Nova Novita (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2015)
This study investigated the influence of intellectual capital disclosure on cost of equity. The empirical research is based on consumer goods companies listed in Indonesia Stock Exchange since 2012-2014. The data used in this study were obtained from the disclosure about information of intellectual capital components I the annual report. The intellectual capital disclosure measured by intellectual capital disclosure index and the cost of equity measured by price earnings growth. The result showed that human capital disclosure has positively significant towards cost of equity, while there is no significant effect between relational capital disclosure, structural capital disclosure and intellectual capital disclosure towards cost of equity. From this results can be inferred that, intellectual capital disclosure and its element: human capital disclosure, relational capital disclosure and structural capital were not considered by the investor specially while making investment decision